Visual Scenarios for addressing the Aspect Interference Problem - Asteasuain, Fernando (2011)
One of the most challenging problems in the aspect-oriented community is known as the aspect interference problem. This situation arises when the behavior to be introduced by two or more aspects is applied at the same point of interest. In order for the developer to resolve this conflict aspects’ interaction and composition must be easy to analyze and manipulate. Under this context, we explore how FVS, a declarative visual language, can address this significant issue by providing a declarative and powerful pointcut model. In addition, FVS allows the possibility of reasoning about violating behavior, that represents a highly valuable information for the developer.